Empire and its Discontents. Circulation of Knowledge and the Emergence of Eugenics in the Late Habsburg Empire - Vojtěch Pojar (Österreichische Zeitschrift für Geschichtswissenschaften, 2023)
The circulation of knowledge poses new questions to the scholarship on eugenics in the Habsburg Empire. Focusing on imperial networks and the cognitive management of imperial diversity, this paper analyses three cases of imperial circulation of eugenic knowledge. It shows that the actors, institutions, and geographies of such circulation varied substantially, depending on the practices out of which the particular type of eugenic knowledge emerged and the functions it served.